PERKEMBANGAN TEGAKAN SETELAH PENEBANGAN DI AREAL IUPHHK-HA PT. BARITO PUTERA, KALIMANTAN TENGAH Growth Development of Logged-Over Stand in the IUPHHK-HA Area of PT. Barito Putera, Central Kalimantan - Istomo .; Rendra Piscestria Nugraha (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Logging activity is one of the factors which changes the structure of forest stand. The objective of this study was to determine the species composition and development of forest stand structure in the IUPHHK-HA area of PT. Barito Putera, Central Kalimantan, especially on the logged over area (LOA) of year 2002, 2007, 2012, and also on the pre-logged area of year 2014 as a comparison (primary forest). Based on observations which have been made, species Shorea leprosula were dominant with different rates of growth in each observation area. Growth development of the stand on logged over area can be said to be normal, because it is in the process toward a normal forest conditions. Potency of the stand before felling in 2014 was 103 trees/ha for the nucleus trees, and 49 trees/ha with volume of 317.25 m3/ha of mature timber (ready to be harvested). On LOA of year 2012, the number of core trees was 77 trees/ha, and 51 trees/ha for mature timber (ready to harvested) with a volume of 584.84 m3/ha. LOA in 2007 exhibited the nucleus trees as many as 93 trees/ha and 53 trees/ha of mature timber (ready to be harvested) with a volume of 427.95 m3/ha. LOA in 2002 exhibited nucleus trees as many as 75 trees/ha and 59 trees/ha of mature timber (ready to harvested) with a volume of 442.41 m3/ha. The differences of growth development in the observation area were probably caused by illegal logging activities that occur in the forest area, and the damage of residual stand (including nucleus trees) as a result of logging and log transportation activities. Logged over forest conditions can be said to be in balance because there were more than 25 nucleus trees/ha remaining, appropriate to the Selective Cutting and Line Planting (TPTJ) regulations, which indicates that the logged over forest can be utilized in subsequent cutting rotation.Key words: composition, Dipterocarp forest, logged-over area, core tree, stand structure.